ANALISIS PERAN KOMPETENSI PEDAGOGIK GURU DALAM MEMPERKUAT MOTIVASI BELAJAR SISWA DI SDN - Annisa’ Sya’diyah; Machfudzil Asror (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
Teacher pedagogical competence plays an important role in improving the quality of learning and strengthening student learning motivation. This competence includes the ability to understand student characteristics, design, implement, and evaluate learning, and develop student potential. Based on the results of initial observations at Banjarbendo elementary school, teachers have attempted to create enjoyable learning through the use of learning methods and media and providing motivation. However, there are still obstacles such as differences in student abilities, less conducive classroom conditions, and limited learning facilities. This study aims to describe the role of teacher pedagogical competence in strengthening student learning motivation and identify supporting and inhibiting factors at Banjarbendo elementary school. This study uses a qualitative approach with a descriptive qualitative research type. The research subjects included teachers of grades V-A and V-B and grade V students of Banjarbendo elementary school. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model which includes data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that teachers have implemented pedagogical competence well through understanding student characteristics, using a variety of learning methods and media, effective communication, and implementing evaluation and follow-up of learning. The application of these competencies can increase student activity, enthusiasm, and involvement in learning. Supporting factors include teacher attention, a variety of methods and media, and providing reinforcement, while inhibiting factors include differences in student abilities, less conducive classroom conditions, limited facilities, and a lack of variety in learning methods. Thus, teacher pedagogical competence plays an important role in strengthening student learning motivation at Banjarbendo elementary school. ABSTRAK Kompetensi pedagogik guru merupakan kompetensi yang berperan penting dalam meningkatkan kualitas pembelajaran dan memperkuat motivasi belajar siswa. Kompetensi ini meliputi kemampuan memahami karakteristik peserta didik, merancang, melaksanakan, dan mengevaluasi pembelajaran, serta mengembangkan potensi siswa. Berdasarkan hasil observasi awal di SDN Banjarbendo, guru telah berupaya menciptakan pembelajaran yang menyenangkan melalui penggunaan metode dan media pembelajaran serta pemberian motivasi. Namun, masih terdapat kendala berupa perbedaan kemampuan siswa, kondisi kelas yang kurang kondusif, dan keterbatasan fasilitas pembelajaran. Penelitian ini bertujuan untuk mendeskripsikan peran kompetensi pedagogik guru dalam memperkuat motivasi belajar siswa serta mengidentifikasi faktor pendukung dan penghambatnya di SDN Banjarbendo. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif kualitatif. Subjek penelitian meliputi guru kelas V-A dan V-B serta siswa kelas V SDN Banjarbendo. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi, kemudian dianalisis menggunakan model Miles dan Huberman yang meliputi pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa guru telah menerapkan kompetensi pedagogik dengan baik melalui pemahaman karakteristik peserta didik, penggunaan metode dan media pembelajaran yang bervariasi, komunikasi yang efektif, serta pelaksanaan evaluasi dan tindak lanjut pembelajaran. Penerapan kompetensi tersebut mampu meningkatkan keaktifan, antusiasme, dan keterlibatan siswa dalam pembelajaran. Faktor pendukung meliputi perhatian guru, variasi metode dan media, serta pemberian penguatan, sedangkan faktor penghambat meliputi perbedaan kemampuan siswa, kondisi kelas yang kurang kondusif, keterbatasan fasilitas, dan kurang bervariasinya metode pembelajaran. Dengan demikian, kompetensi pedagogik guru berperan penting dalam memperkuat motivasi belajar siswa di SDN Banjarbendo.